IMAGINING AND ENCOUNTERING THE OTHER IN MANCHESTER AND BARCELONA: THE NARRATIVES OF POLISH MIGRANT WOMEN (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2016)
In the context of post-2004 European migration, Polish migrants encounter super-diverse population (Vertovec 2007) in terms of different ethnicities, nationalities, cultures, religions, languages and social classes. Drawing on narrative interviews and focus groups with Polish migrant women, I explore my research participants’ imaginaries aboutthe classed, raced and gendered Other upon their arrival in Manchester and Barcelona. I explore the constructions of the classed English Other different from the imagined upper class and white British society; ‘closed’ Catalans contrasting the stereotypical perceptions of open and friendly Spaniards and foreigners; and ambivalent perceptions of black andOriental others. I use the postcolonial critique in de-coding some of these constructions. I stress the importance of the context and space in which these perceptions may have developed and reinforced. I also explore the possibility of changing perceptions and the emergence of conviviality understood as a practical and dynamic process, which emerges fromroutine interaction between the recent arrivals and established individuals, not necessarily free from tensions. My work contributes to a better understanding of everyday social relations as it introduces a cross-cultural comparative and gendered approach to research on conviviality. Furthermore, instead of focusing on majority-minority relations, it explores encounters between post-2004 migrants not only with the native population but also with settled ethnic minorities and other migrants with attention to whiteness and deeply rooted classed and racialised perceptions of the Other.
Keywords: Barcelona; conviviality; encounter; Manchester; Polish migrant women; racialisation; super-diversity; whiteness